Corrosão em estacas metálicas de torres de energia elétrica - VILHENA, Alexandre Evangelista Rodrigues (Rede Latino-Americana de Materiais, 2019)
In order to maintain the quality and continuity of the power supply it is essential to monitor the integrity of the structure of the transmission towers usually executed in steel. This study evaluated soil corrosivity in the Amazon region in the Vila do Conde-Tucuruí stretch, state of Pará. The resistivity, potential soil structure, redox potential, pH, chloride, sulphate and sulfate concentration, besides the Steinrath index and the quantification of the soil corrosivity through the installation of test specimens in the studied soil. The data were collected in the dry and rainy period while the specimens were removed after 12 months of exposure. The soils of the region presented resistivity higher than 20 kΩ.cm, characterizing as few corrosives; the redox potential of 100 to 300 mV indicated mild to moderately corrosive soils; the potential soil structure remained in the range of -0.4 to -0.7 V/ECS being within the range considered normal; the Steinrath index classified the soils into little corrosive to non-corrosive and the corrosion rates of the test specimens indicated high corrosion at 3 meters depth. Based on the results of each evaluation method used it can be verified that the soil corrosivity increases with the depth, besides being favorable to the attack of microbiological corrosion.